Loker Penyimpanan Kunci Laboratorium Otomatis dengan RFID Berbasis Raspberry Pi - Rizki Faulianur; Inzar Salfikar; Ahyar Mustafa (J-Innovation, 2025)
In Vocational colleges, the high activity of students in the laboratory for practical activities, research, and others makes the use of the laboratory more optimal so that it is difficult to monitor its use. This results in a lack of information on the track record of laboratory use. So if the key and laboratory equipment are lost, it is very difficult to identify. The laboratory key security system based on Radio Frequency Identification (RFID) and Raspberry Pi is one solution that can be used for a security system compared to the conventional physical locker key system. This system uses Raspberry Pi as the main controller to control the lock mechanism on the locker. This system aims to provide convenience and security in the use of lockers using miniature computing technology. This system consists of Raspberry Pi as a control center, solenoid lock door to move the lock mechanism, LCD screen to display information to users, and RFID as a user authentication method before opening the locker. This tool is also able to inform the day and time of taking the locker key recorded on the website. By using this system, users can easily access the locker and can more easily find out the track record of taking the laboratory key. The results of the study, from 7 users registered in the system, all of them successfully opened the locker with a success rate of 100%. The response time to open and close the locker door is a maximum of 60 seconds. Users who access the locker can be recorded on the website regarding the date and time of locker access.